Über Funktionen, die keine nullgleiche dividierte Differenz besitzen - Kirjatsky, E. (Lithuanian Mathematical Journal, 1963)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Э. Кирьяцкий. О функциях с разделенной разностью, отличной от нуля E. Kirjackis. Funkcijos, kurių padalytasis skirtumas nėra lygus nuliui